PENGARUH AIR LAUT PADA MASA PERAWATAN TERHADAP INFILTRASI ION KLORIDA PADA BETON DENGAN PENAMBAHAN FLY ASH 12,5% - Laras Ari Indriyanto; Ashar Saputra; Djoko Sulistyo (Prodi Teknik Sipil FT Universitas Sebelas Maret, 2020)
The use of concrete material which dominates Indonesian construction industry is not only because its compilers are easy to get, but also because it has high durability. Anyhow, concrete structure might have high risk of damage in aggressive region and open space. Sulfate attack will form calcium sulfoaluminate where the volume of calcium aluminate is higher than concrete’s, so its volume increases and damages the connection between aggregate and cement which work as bonding. One of applicative and easy-to-get technology in preventing the effect of sulfate attack is by using additional material, pozzolan. It consists of fly ash and Blast Furnace Cement BFC which come from iron ore refining process. This research aims at finding out the effect of sea water in immersion phase and age variation towards compressive strength, split strength, flexural tensile strength and concrete permeability as well as the depth of chloride ion infiltration in normal concrete by adding fly ash. Chloride ion infiltration testing is done by soaking 150x150x150 mm cube using sea water with various period for 28, 60 and 90 days and then it will be sprayed by AgNO3 solution to know the depth of absorbed chloride ion infiltration. Chloride ion infiltration of concrete using sea water happens in 0-1.4 cm depth up to 90 days management. The addition of fly ash 12.5% makes the depth of chloride ion infiltration become smaller than using OPC for each immersion age variation.